2013
DOI: 10.1590/s1806-83242013000100019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microhybrid resin and etching times on bleached enamel for the bonding of ceramic brackets

Abstract: The aim of this study was to evaluate the shear bond strength (SBS) of polycrystalline ceramic brackets (PCB) bonded after bleaching treatment using different composite resins and enamel etching times. A total of 144 bovine incisors were randomly divided into two study groups (n = 72, each) as follows: G1, enamel bleached with 35% hydrogen peroxide, and G2 (control group), enamel unbleached. After the bleaching treatment, the samples were stored in artificial saliva for 14 days. These groups were further divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…In the literature previous reports showed contradicting results. Different previous studies showed an insignificant [26, 27] or significant [28] influence of adhesive system on ARI scores. Moreover, both insignificant [10, 17, 29] and significant [11] effects of base design on ARI scores have been previously reported.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature previous reports showed contradicting results. Different previous studies showed an insignificant [26, 27] or significant [28] influence of adhesive system on ARI scores. Moreover, both insignificant [10, 17, 29] and significant [11] effects of base design on ARI scores have been previously reported.…”
Section: Discussionmentioning
confidence: 97%
“…reported a reduction in bond strength of polycrystalline ceramic brackets even after 14 days of bleaching. [22]…”
Section: Discussionmentioning
confidence: 99%
“…This increase in translucency helps in achieving maximum bond strength in ceramic brackets. Leily Macedo Firoozmand in 2013 suggested that sapphire brackets have more strength with composite [15].…”
Section: Discussionmentioning
confidence: 99%